Economic Preferences across Generations and Family Clusters: A Large-Scale Experiment - Shyamal Chowdhury; Matthias Sutter; Klaus F. Zimmermann (Institute of Labor Economics (IZA), 2020)
Economic preferences are important for lifetime outcomes such as educational achievements, health status, or labor market success. We present a holistic view of how economic preferences are related within families. In an experiment with 544 families (and 1,999 individuals) from rural Bangladesh we find a large degree of intergenerational persistence of economic preferences. Both mothers' and fathers' risk, time and social preferences are significantly (and largely to the same degree) positively correlated with their children's economic preferences, even when controlling for personality traits and socio-economic background data. We discuss possible transmission channels for these relationships within families and find indications that there is more than pure genetics at work. Moving beyond an individual level analysis, we are the first to classify a whole family into one of two clusters, with either relatively patient, risktolerant and pro-social members or relatively impatient, risk averse and spiteful members. Socio-economic background variables correlate with the cluster to which a family belongs to.
Keywords: C90; D1; D90; D81; D64; J13; J24; J62; 330; economic preferences within families; intergenerational transmission of preferences; time preferences; risk preferences; social preferences; family clusters; socio-economic status; Bangladesh; experiment